The Relationship Between Health Literacy and Health-Related Quality of Life in Students - Mahnaz Khaleghi; Farkhondeh Amin Shokravi; Noshin Peyman (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: Health literacy is a cognitive and social skill that determines people's motivation and ability to acquire, understand, and use health information to promote and maintain good health. The aim of this study is to determine health literacy and its relationship with health-related quality of life in students of the Islamic Azad University, Shahr-e-Rey branch Methods: In this cross-sectional correlational study, health literacy and quality of life of 278 students were measured. Randomized multistage sampling method was applied. Functional Health Literacy of Adults (TOFHLA), and SF-12(short form of SF-36) were used to collect the data. For data analysis, SPSS 16 software, descriptive statistics, ANOVA, and regression statistical tests were used. Results: The Findings showed that the average health literacy score was 70.35±18/25, which 25/2 % (70 people) had inadequate health literacy, 21.9 %  (61 people) had border health literacy, and 52/9 % (147 people) had adequate health literacy. The mean score of quality of life for students was 36/99±5/80; which  3/23 % (n = 9), 43/88 % (n=61), 54/31 % (151 people) had poor, moderate, and good QOL respectively. The results of this study showed health literacy has a significant relationship with the overall quality of life (P>0/05), physical (P >0/05), and psychological (P >0/05) dimensions. Conclusion: Students' health literacy is associated with their quality of life and its dimensions. Therefore, in order to promote their educational performance, which causes a better quality of life, it is important to concentrate on improving QOL of People through increasing their health literacy.